Evaluating service quality in Indonesian rural tourism: The RURALQUAL model approach - Fety Nurlia Muzayanah; Rediawan Miharja; Agustifa Zea Tazliqoh (Journal of Enterprise and Development (JED), 2024)
Purpose — The purpose of this study is to evaluate service quality using the RURALQUAL model and examine its relationship with customer satisfaction and customer experience.Method — The research method employed in this study is quantitative research using Structural Equation Modeling, specifically Partial Least Squares (PLS-SEM). The variables investigated include service quality (X) as the independent variable, customer experience (Y) as the intervening variable, and customer satisfaction (Z) as the response variable. The population for this study consists of tourists visiting Wanayasa Rural Tourism in Purwakarta. The sampling method used to select participants is non-probability sampling, specifically the purposive sampling technique. A total of 344 Wanayasa tourists were included as samples in this study.Result — This study discovered that there is a notable impact on customer experience and customer satisfaction when it comes to service quality. Additionally, customer experience can act as a mediator between service quality and customer satisfaction.Novelty — This research applies RURALQUAL model approach to measure service quality in rural tourism in Wanayasa, Purwakarta, Indonesia.